Genome-wide analysis of oxylipins and oxylipin profiles in a pediatric population - Buckner, Teresa; Johnson, Randi K.; Vanderlinden, Lauren A.; Carry, Patrick M.; Romero, Alex; Onengut-Gumuscu, Suna; Chen, Wei-Min; Kim, Soojeong; Fiehn, Oliver; Frohnert, Brigitte I.; Crume, Tessa; Perng, Wei; et al. (Frontiers in Nutrition, 2023)
Background. Oxylipins are inflammatory biomarkers derived from omega-3 and -6 fatty acids implicated in inflammatory diseases but have not been studied in a genome-wide association study (GWAS). The aim of this study was to identify genetic loci associated with oxylipins and oxylipin profiles to identify biologic pathways and therapeutic targets for oxylipins. Methods. We conducted a GWAS of plasma oxylipins in 316 participants in the Diabetes Autoimmunity Study in the Young (DAISY). DNA samples were genotyped using the TEDDY-T1D Exome array, and additional variants were imputed using the Trans-Omics for Precision Medicine (TOPMed) multi-ancestry reference panel. Principal components analysis of 36 plasma oxylipins was used to capture oxylipin profiles. PC1 represented linoleic acid (LA)- and alpha-linolenic acid (ALA)-related oxylipins, and PC2 represented arachidonic acid (ARA)-related oxylipins. Oxylipin PC1, PC2, and the top five loading oxylipins from each PC were used as outcomes in the GWAS (genome-wide significance: p<5x10-8). Results. The SNP rs143070873 was associated with (p<5x10-8) the LA-related oxylipin 9-HODE, and rs6444933 (downstream of CLDN11) was associated with the LA-related oxylipin 13 S-HODE. A locus between MIR1302-7 and LOC100131146, rs10118380 and an intronic variant in TRPM3 were associated with the ARA-related oxylipin 11-HETE. These loci are involved in inflammatory signaling cascades and interact with PLA2, an initial step to oxylipin biosynthesis. Conclusion. Genetic loci involved in inflammation and oxylipin metabolism are associated with oxylipin levels.